COMPUTER SIMULATION OF DEFECT STRUCTURE IN SILLIMANITE AND MULLITES - Wondraczek L.; Heide G.; Kilo M.; Nedeljkovic N.; Borchardt G.; Jackson R.A. (My University, 2002)
Defect structure and the defect formation in mullites and sillimanites have been investigated using computer simulation techniques. From point defect chemistry and computer simulations, oxygen vacancies are identified as the majority defect responsible for oxygen transport in mullite. The defect formation energies are between 3 and 4 eV. Using supercell calculation methods, the random structure is identified to be stable in mullites, whereas the ordered structure can be confirmed to be more stable in sillimanite. An energy of 0.7-1.0 eV for the association of oxygen vacancies with cations is estimated.
Keywords: MULLITE; SILLIMANITE; COMPUTER SIMULATION; DEFECT ENERGY